Efficiency of the removal of microcystin-LR by UV-radiation and hydrogen peroxide (2020)
Due to the harmful effects associated with the presence of microcystin-LR (MC-LR) cyanotoxin, photo-degradation assays were performed in natural and distilled water using the combined action of ultraviolet (UV) radiation and hydrogen peroxide (H2O2). The effect of H2O2 content and UV irradiance was evaluated and optimized using a multilevel factorial design in distilled water spiked with 20 µg L-1 MC-LR. The coupled UV/H2O2 system under optimal operating conditions (0.63 mW cm-2 irradiance and 30 mg L-1 H2O2) was more effective than the individual action of UV irradiance or H2O2 content for 30 min of treatment time, since a reduction of 97.78% of MC-LR was achieved. After optimizing the operating conditions, they were applied for natural water, obtaining MC-LR removals similar to those achieved with distilled water (99.59 and 99.73%, respectively), reaching a final MC-LR concentration in both matrices well below the maximum recommended limit established by WHO for MC-LR in drinking water, fixed at 1 µg L-1. 15 mg L-1 of H2O2 were also tested, and although 98.08% of MC-LR elimination was found for a reaction time of 60 min, WHO advisable limit was not surpassed. The UV/H2O2 process could be considered as an alternative to the conventional processes water facilities are operating with to tackle the problem of fresh water pollution with cyanotoxins, providing the accomplishment of the whole set of water quality standards included in the legislation